The EARLY MARRIAGE IN ISLAMIC LAW: ADDRESSING SOCIAL AND ETHICAL CHALLENGES OF LEGISLATION - Millati, Najmatur Radhwa; Assidqi, Muhammad Raffa; Rosalia, Ami; Suresman, Edi (Cahaya Ilmu Bangsa Institute, 2025)
Abstract Early marriage remains a prevalent phenomenon in various regions of Indonesia. This study aims to analyze the issue from the perspectives of Islamic law and national legislation, focusing on the underlying factors, as well as the social and health consequences and their relationship with legal and ethical values. The method utilized is a qualitative approach, which includes a literature review and the distribution of questionnaires to adolescent groups. The findings indicate that early marriage is influenced by several factors, such as economic pressure, family expectations, cultural values, and instances of marriage resulting from unplanned pregnancies, often referred to as